Bimetallic MOFs-Derived Metal Oxides Co3O4/SnO2 Microspheres for Ultrahigh Response n-Butanol Gas Sensors - Zhang, Zhenkai (Langmuir : the ACS journal of surfaces and colloids, 2024)
The construction of p-n heterojunctions is expected to be one of the effective means to improve gas sensitivity. In this research, p-n heterojunctions are successfully constructed by metal oxides derived from metal-organic frameworks (MOFs). MOFs-derived bimetallic Co3O4/SnO2 microspheres are prepared by precipitation. Gas-sensing performance shows that the Co3O4/SnO2 sensor exhibits an extremely high response (Ra/Rg = 641) to 20 ppm of n-butanol at 200 °C, which is 19 times that of pristine SnO2. It can detect n-butanol gas at low concentrations, has good selectivity to alcohol gas, and reduces the interference of benzene gas. The improved gas sensitivity can be attributed to the formation of a stable heterojunction between Co3O4 and SnO2, resulting in a greater resistance change of Co3O4/SnO2. Co3O4/SnO2 inherits the characteristic of high specific surface area of MOFs, which provides abundant sites for the reaction of the target gas and oxygen molecules. Finally, the gas-sensing mechanism of the Co3O4/SnO2-based sensor is discussed in detail